Regulation of platelet guanylyl cyclase by collagen: evidence that Glycoprotein VI mediates platelet nitric oxide synthesis in response to collagen - Riba, Rocio; Sharifi, Marzieh; Farndale, Richard W.; Khalid, M. Naseem (Thrombosis and Haemostasis, 2005)
The molecular regulation of nitric oxide synthase (NOS) in blood platelets is an uncharacterised area of platelet biology. We investigated the mechanism of collagen-stimulated NO synthesis in platelets. Our aim was to identify the key collagen receptor and downstream signalling mechanisms linking collagen to NOS activation. Collagen and the GpVI-specific platelet activator collagen-related peptide (CRP-XL) stimulated NO synthesis, as evidenced by increased [3H]L-citrulline production, and cyclic GMP (cGMP) formation. After platelet activation by collagen and CRP-XL was normalised, we found no differences in NOS activation or cGMP formation in response to these agonists. Blocking the interaction of collagen with integrin α2β1, a second collagen receptor, failed to affect NOS activation by collagen. These data indicate that collagen-induced NO synthesis is linked to GpVI activation. cGMP formation in response to collagen and CRP-XL required increased intracellular Ca2+, Src family kinases,phosphatidylinositol 3-kinase (PI3-K) and protein kinase C. By comparison, Gp VI-independent cGMP formation induced by thrombin was Src kinase-dependent, but was independent of PI3-K and PKC. Thus the mechanisms of collagen- and CRP-XL-induced NOS activation were identical, but distinct from that of thrombin. Platelet activation in response to collagen leads to secretion of adenosine diphosphate (ADP) and thromboxaneA2 (TxA2). Our results demonstrate that collagenstimulated cGMP synthesis was enhanced significantly by platelet- derived ADP and TxA2. These results reveal that collagen stimulates platelet NOS activation through a specific Ca2+-dependent GpVI receptor signalling cascade,and demonstrate that collagen-induced cGMP accrual requires the release of secondary platelet agonists.
Keywords: Platelet; nitric oxide; collagen; GpVI; cGMP